2008
DOI: 10.1109/tbme.2007.908069
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Forces of Cutting With Scissors

Abstract: Modeling forces applied to scissors during cutting of biological materials is useful for surgical simulation. Previous approaches to haptic display of scissor cutting are based on recording and replaying measured data. This paper presents an analytical model based on the concepts of contact mechanics and fracture mechanics to calculate forces applied to scissors during cutting of a slab of material. The model considers the process of cutting as a sequence of deformation and fracture phases. During deformation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 18 publications
1
25
0
Order By: Relevance
“…This was verif ed by measuring the length of the slit in the sample after cut completion. A fracture toughness value of 4.36 kJ m −2 was obtained using (20), comparable to that found in other literature [19]. Error bars are included to convey the force resolution, which improves toward the end of the cut as the blades are closed by the scissor handles.…”
Section: Fracture Toughness Estimationsupporting
confidence: 81%
See 1 more Smart Citation
“…This was verif ed by measuring the length of the slit in the sample after cut completion. A fracture toughness value of 4.36 kJ m −2 was obtained using (20), comparable to that found in other literature [19]. Error bars are included to convey the force resolution, which improves toward the end of the cut as the blades are closed by the scissor handles.…”
Section: Fracture Toughness Estimationsupporting
confidence: 81%
“…Using (19) the external work done due to combined fracture and friction, W ff , was obtained by integrating under the fracture forcedisplacement profi e in f gure 13. Similarly, the external work done due to friction only, W f , was obtained and subtracted from W ff resulting in work done due to material fracture only.…”
Section: Fracture Toughness Estimationmentioning
confidence: 99%
“…Most of the work featured the slicing of test samples using an instrumented cutting implement like a guillotine (Atkins and Mai, 1979), a blade (Lake and Yeoh, 1978), or a pair of scissors (Sim et al, 1993). In haptics, fracture mechanics have enabled the modelling of the forces required to cut through soft tissue with scissors (Mahvash et al, 2008). Related to biomechanics, Pereira et al (1997) have ranked the fracture toughness of various mammalian soft tissues using a scissor testing rig.…”
Section: Introductionmentioning
confidence: 99%
“…This technology would give that advantage back to the operating surgeon. Haptic feedback, despite the argument made by Shah et al, has been shown to reduce of tissue injury and suture breakage, while at the same time maintain a reasonable operating time, under an experienced surgeon [33][34][35][36][37].…”
Section: Discussionmentioning
confidence: 98%